1996
DOI: 10.1680/geot.1996.46.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Fast shearing of pre-existing shear zones in soil

Abstract: The paper presents results from a laboratory investigation into the in¯uence of fast rates of displacement on the residual strength of soil. This in¯uence was studied in the ring shear apparatus. Shear zones were formed by slow drained shearing and then tested at alternately fast and slow rates of displacement. Results from a wide range of natural soils are presented. All soils show initially an increase in strength when resheared at fast rates of displacement. The strength then tends to decrease with fast dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
135
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(178 citation statements)
references
References 20 publications
18
135
0
5
Order By: Relevance
“…However, there are no published rate and state friction parameters from laboratory experiments on landslide material at relevant in situ stress conditions. Because the slip surfaces of landslides and faults are both governed by frictional sliding (14), we select nominal rate and state parameter values from the fault and soil mechanics literature (Table S1) (18,(44)(45)(46)(47)(48)(49). Because our focus here is on understanding the overall patterns of landslide motion, we consider small errors introduced by uncertainty in parameter values to be acceptable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are no published rate and state friction parameters from laboratory experiments on landslide material at relevant in situ stress conditions. Because the slip surfaces of landslides and faults are both governed by frictional sliding (14), we select nominal rate and state parameter values from the fault and soil mechanics literature (Table S1) (18,(44)(45)(46)(47)(48)(49). Because our focus here is on understanding the overall patterns of landslide motion, we consider small errors introduced by uncertainty in parameter values to be acceptable.…”
Section: Methodsmentioning
confidence: 99%
“…For the slow-moving landslide model runs, we use a larger d c that is consistent with fieldbased estimates of friction parameters on faults (35). We select μ 0 that characterizes weak, clay-rich materials (45,46,48,49) that are common to slow-moving landslides with well-developed slip surfaces (2). The shear modulus and shear wave speed are based on values measured for the Jurassic and Cretaceous Franciscan Complex, Northern California (50), a region well known for slow-moving landslide activity (5), and are notably lower than values reported for deep faults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, he is addressing the issue of an initial increase in shear strength: that is, from slow residual (static) to the threshold and then to the fast peak value (Tika et al, 1996). As he states, this initial increase is due to 'viscous and suppressed-dilatancy effects'.…”
Section: Author's Replymentioning
confidence: 99%
“…The relationship between the residual strength and the shear displacement rate for various soils has been examined using RDBST apparatus (Kenney, 1967;Ramiah et al, 1970;Skempton, 1985;Mitachi et al, 2003) and RST apparatus (Lemos et al, 1985: Skempton, 1985Yatabe et al, 1991;Tika et al, 1996;Suzuki et al, 2000). Skempton (1985) concluded that the variation in strength within a usual range of slow laboratory test (0.002-0.01 mm/min) was negligible.…”
Section: In‰uence Of Shear Displacement Rate On Residual Strength Of mentioning
confidence: 99%